2020
DOI: 10.1111/jeb.13588
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for rapid downward fecundity selection in an ectoparasite (Philornis downsi) with earlier host mortality in Darwin’s finches

Abstract: Fecundity selection is a critical component of fitness and a major driver of adaptive evolution. Trade‐offs between parasite mortality and host resources are likely to impose a selection pressure on parasite fecundity, but this is little studied in natural systems. The ‘fecundity advantage hypothesis’ predicts female‐biased sexual size dimorphism whereby larger females produce more offspring. Parasitic insects are useful for exploring the interplay between host resource availability and parasite fecundity, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 88 publications
(170 reference statements)
0
21
0
Order By: Relevance
“…Long term studies on Darwin's finches showed that in recent years P. downsi infests nests earlier in the breeding cycle of the hosts (Cimadom et al ) and thus leads also to earlier host death. Interestingly, a recent study suggests that earlier host death due to P. downsi selects for faster pupation and thereby for smaller body size and hence lower fecundity in female adult flies (Common et al ), which over time could ease harm of P. downsi to Galápagos landbirds.…”
Section: Discussionmentioning
confidence: 99%
“…Long term studies on Darwin's finches showed that in recent years P. downsi infests nests earlier in the breeding cycle of the hosts (Cimadom et al ) and thus leads also to earlier host death. Interestingly, a recent study suggests that earlier host death due to P. downsi selects for faster pupation and thereby for smaller body size and hence lower fecundity in female adult flies (Common et al ), which over time could ease harm of P. downsi to Galápagos landbirds.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2004, there have been measurable shifts in P. downsi and host behaviour on both islands. Philornis downsi oviposition and hatching have shifted towards earlier in the host incubation period on Santa Cruz Island, whereas P. downsi hatching (and perhaps oviposition) occurs during chick feeding on Floreana [ 35 , 52 , 88 ]. On Floreana Island, the proportion of hybrid tree finches in the population increased to 55% in 2006 and has since remained at approximately 40% [ 43 , 45 ], and higher admixture (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Once the nesting event had finished (i.e. the offspring had died or fledged), as confirmed by our routine nest monitoring, the nest was immediately collected from the field, stored in a plastic bag and transported to our on-site laboratory later in the day to count the number of P. downsi larvae, pupae and puparia [ 52 ]. Generally, all P. downsi were counted within 6 h and a maximum of 24 h post-nest collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexible associations may evolve distinct functional roles that eventually support speciation, as presumably in Drosophila flies and Cephalodia beetles, where specific microbial communities are associated with host species in ways that support exclusive dietary niches (Martinson et al, 2017;Blankenchip et al, 2018). Similarly, the parasitic habit of P. downsi is an evolved trait that is thought to be derived from ancestral saprophagy, where larvae developed by scavenging on excrement and organic debris in avian nests, (Couri et al, 2007;Dudaniec and Kleindorfer, 2016;Common et al, 2020). Radiation into this new dietary niche probably required the adoption of and adaptation to a new set of gut bacteria, which may have eventually contributed to S8).…”
Section: Diet As a Moderator Of P Downsi Gut Microbiome Across Life Stagesmentioning
confidence: 99%